A study on the safety and tolerability of mycophenolate mofetil in patients with connective tissue disease - Das, Subham; Padhan, Prasanta (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Connective tissue disorders (CTD) are mostly due to inflammatory and fibrotic tissue injury. Glucocorticoids and immunomodulators though useful but are toxic. Mycophenolate mofetil (MMF) is now being used successfully in many autoimmune diseases, but the safety of MMF in CTD patients is yet to be conclusively established. Methods: The study was a retrospective record based observational one in patients of CTD satisfying the predetermined inclusion criteria. Various safety parameters were noted down from the observed records and analysed accordingly. Results: The 120 case records of CTD patients were analysed for a specific set of safety parameters over the preceding one year. Diarrhoeal attacks were the most commonly encountered side effect (38.3%) of long term patients who were on mycophenolate therapy followed by infection. Conclusions: Mycophenolate was found to be generally well tolerated in CTD patients with few reports of adverse events, but larger clinical trials are needed to conclusively establish its safety.